What was the Hindenburg? - Pascal, Janet B. (What was--?, 2014)
Describes the history of the Hindenburg airship and its fateful flight from Germany to the United States in 1937, when it burst into flames upon arrival, and details the decline of the use of airships for commercial transportation.